Preparation method of high-temperature-resistant anti-degumming environment-friendly degradable adhesive tape
By adding modified talc, alkaline lignin and acrylic to the pressure-sensitive adhesive of biodegradable tape, the problem of tape degumming at high temperatures is solved, and its heat resistance and practical application performance are significantly improved.
Patent Information
- Application Number
- CN202411262977.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-03-07
AI Technical Summary
Existing biodegradable tapes are prone to degumming under high temperature action, which limits their practical application.
Modified talc powder and alkali lignin are added to the pressure-sensitive adhesive as the viscosity enhancer, and acrylic acid is introduced as the new monomer component to improve the heat resistance of the pressure-sensitive adhesive.
By enhancing the heat resistance of pressure-sensitive adhesive, the occurrence of degumming at high temperatures is reduced and the practical application performance of tape is improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of adhesive tapes, and more specifically, to a method for preparing a high temperature resistant and anti-debonding environmentally friendly degradable adhesive tape. Background Art
[0002] At present, with the increasing consumption of oil resources, based on the demand for sustainable development, it is necessary to vigorously develop degradable plastic products. Among the existing plastic products, tapes are widely used in the packaging industry because of their convenience and low cost. The development of degradable tape products with good performance is of great significance to achieving the goal of sustainable development.
[0003] In the related art, there is a biodegradable tape, which includes a substrate layer and a pressure-sensitive adhesive coated on the surface of the substrate layer. The components of the substrate layer include PBAT, PLA chain extender and filler, and the pressure-sensitive adhesive is a polyacrylate pressure-sensitive adhesive. The polyacrylate pressure-sensitive adhesive is prepared according to the following method: an acrylic acid monomer and an initiator are added to ethyl acetate, stirred and heated at 80°C for 6 hours, cooled to room temperature, diluted and a cross-linking agent is added to obtain a pressure-sensitive adhesive. The ratio of acrylic acid monomer to ethyl acetate is 1kg:2.6L, and the acrylic acid monomer is isooctyl acrylate, butyl acrylate and vinyl acetate mixed in a weight ratio of 3:1:1. The initiator is AIBN, and the amount used is 0.5% of the total weight of the acrylic acid monomer.
[0004] Regarding the above-mentioned related technologies, the inventors believe that although the pressure-sensitive adhesive in the related technologies has certain bonding properties, its high temperature resistance is still relatively limited. It is easy to debond under high temperature, which limits the practical application of this tape. Summary of the invention
[0005] In the related art, due to the limited high temperature resistance of pressure sensitive adhesive, it is easy to debond under the influence of high temperature, thus limiting the practical application of the tape. In order to improve this defect, the present application provides a method for preparing a high temperature resistant and anti-debonding environmentally friendly degradation tape.
[0006] The present application provides a method for preparing a high temperature resistant and anti-debonding environmentally friendly degradable adhesive tape, which adopts the following technical solution: A method for preparing a high temperature resistant and anti-debonding environmentally friendly degradation tape comprises the following steps: (1) Preparation of substrate layer: blending a degradable resin, a filler and a chain extender, and then melt-extrude the mixture, and then water-cooling and granulating the mixture to obtain a degradable composite, and then blowing the degradable composite to obtain a substrate layer for later use; the degradable resin includes PBAT and PLA; (2) Preparation of pressure-sensitive adhesive: adding acrylic monomer, initiator and tackifier to ethyl acetate, stirring and heating first, and then adding cross-linking agent after cooling and dilution to obtain pressure-sensitive adhesive; the tackifier includes modified talcum powder and alkali lignin, the modified talcum powder is talcum powder with allyl groups grafted on the surface of particles, the acrylic monomer contains at least one acrylate and 1.3-2.5wt% of acrylic acid, the amount of modified talcum powder is 2.2-2.8% of the total weight of acrylic monomer, and the amount of alkali lignin is 1.2-1.6% of the total weight of acrylic monomer; (3) coating the pressure-sensitive adhesive onto the surface of the substrate layer to obtain a semi-finished adhesive tape, and drying the semi-finished adhesive tape to obtain a high-temperature resistant and anti-debonding environmentally friendly degradable adhesive tape.
[0007] By adopting the above technical scheme, the present application adds modified talcum powder and alkali lignin as tackifiers in the pressure-sensitive adhesive, and introduces acrylic acid as a new monomer component. The allyl group on the surface of the modified talcum powder can copolymerize with the acrylic acid monomer, and the alkali lignin can form a relatively strong hydrogen bond with the acrylic acid copolymer, and the acrylic acid can improve the degree of crosslinking between the monomers and the degree of crosslinking between the monomers and the allyl group on the surface of the modified talcum powder. In addition, the addition of modified talcum powder can also enhance the initial adhesion of the pressure-sensitive adhesive, overcome the negative impact of the addition of acrylic acid on the initial adhesion of the pressure-sensitive adhesive, and maintain the product performance of the pressure-sensitive adhesive. Under the joint action of the tackifier and acrylic acid, the pressure-sensitive adhesive of the present application can show higher heat resistance, so that it is difficult for the adhesive tape to debond after being affected by high temperature, overcome the defect of poor heat resistance of the adhesive tape in the related art, and is conducive to the practical application of the adhesive tape.
[0008] Preferably, the modified talc is prepared according to the following method: (1) adding talc to a sodium hydroxide solution, stirring and heating at 90-95° C. for 4-6 hours, and then centrifuging, and vacuum drying the separated solid to obtain hydroxylated talc; (2) Adding hydroxylated talc to an ethanol aqueous solution, adding glacial acetic acid to adjust the pH, then adding a silane coupling agent, stirring for 4-6 hours in a water bath at 80-85° C., cooling to room temperature after stirring, and obtaining modified talc after centrifugal separation, washing and vacuum drying; the amount of the silane coupling agent is 5-20% by weight of the hydroxylated talc, and the silane coupling agent has an allyl group in its molecule.
[0009] By adopting the above technical scheme, the present application first uses a sodium hydroxide solution to treat talc powder so that the surface of the talc powder has a certain amount of hydroxyl groups to obtain hydroxylated talc powder, and then uses a silane coupling agent to react with the hydroxylated talc powder to introduce allyl groups into the surface of the hydroxylated talc powder to obtain modified talc powder.
[0010] Preferably, the silane coupling agent includes KH570.
[0011] By adopting the above technical solution, KH570 can introduce allyl groups into the surface of hydroxylated talc, thereby obtaining modified talc.
[0012] Preferably, the silane coupling agent is prepared by mixing KH570 and docosyltriethoxysilane in a weight ratio of 1:(1.2-3.4).
[0013] By adopting the above technical scheme, the present application optimizes the composition of the silane coupling agent, and adds docosyl triethoxysilane in addition to KH570. Docosyl triethoxysilane introduces a long carbon chain with an allyl group to the surface of the hydroxylated talc. After participating in the copolymerization, this carbon chain can reduce the glass transition temperature of the copolymer, thereby enhancing the surface wetting ability of the pressure-sensitive adhesive, which helps to further improve the initial adhesion of the pressure-sensitive adhesive.
[0014] Preferably, the silane coupling agent is prepared by mixing KH570 and docosyltriethoxysilane in a weight ratio of 1:(2.1-3.4).
[0015] By adopting the above technical solution, the present application optimizes the composition of the silane coupling agent, which helps to further improve the initial adhesion of the pressure-sensitive adhesive.
[0016] Preferably, the amount of the silane coupling agent is 12-20% by weight of the hydroxylated talc.
[0017] By adopting the above technical solution, the present application optimizes the dosage of the silane coupling agent, which helps to fully realize the modification treatment of talc.
[0018] Preferably, the initiator is one of BPO and AIBN.
[0019] By adopting the above technical solution, the present application optimizes the type of initiator. Among the two initiators, BPO is more helpful to improve the initial adhesion of the pressure-sensitive adhesive.
[0020] Preferably, the initiator is BPO, and the amount of BPO used is 0.75-1.10% of the total weight of the acrylic monomers.
[0021] By adopting the above technical solution, the present application optimizes the amount of BPO used as an initiator, which helps to fully improve the initial adhesion of the pressure-sensitive adhesive.
[0022] Preferably, the acrylic monomer contains 0.5-2.5 wt % of hydroxyethyl acrylate.
[0023] By adopting the above technical scheme, the present application preferably selects acrylic monomers including hydroxyethyl acrylate. The addition of hydroxyethyl acrylate not only improves the cohesion of the system and the adhesion of the pressure-sensitive adhesive, but also has a certain effect on improving the initial adhesion of the pressure-sensitive adhesive.
[0024] Preferably, the acrylic monomer contains 1.5-2.5 wt % of hydroxyethyl acrylate.
[0025] By adopting the above technical solution, the present application optimizes the dosage of hydroxyethyl acrylate, which helps to fully improve the initial adhesion and sustained adhesion of the pressure-sensitive adhesive.
[0026] In summary, this application has the following beneficial effects: 1. Under the joint action of the tackifier and acrylic acid, the pressure-sensitive adhesive of the present application can exhibit higher heat resistance, making it less likely for the tape to debond after being affected by high temperature, thereby overcoming the defect of poor heat resistance of the tape in the related art. Moreover, the adhesiveness and tack retention of the tape can be balanced, and it has good bonding properties, which is beneficial to the practical application of the tape.
[0027] 2. The present application preferably selects a specific type of silane coupling agent, and selects docosyltriethoxysilane, which can introduce a long carbon chain with an allyl group into the surface of hydroxylated talc. After participating in the copolymerization, this carbon chain can reduce the glass transition temperature of the copolymer, thereby enhancing the surface wetting ability of the pressure-sensitive adhesive, which helps to further improve the initial adhesion of the pressure-sensitive adhesive. DETAILED DESCRIPTION
[0028] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.
[0029] Preparation example of modified talc
[0030] The following is an explanation using Preparation Example 1.
[0031] Preparation Example 1 In this preparation example, modified talcum powder was prepared according to the following method:
[0032] (1) adding 5000 mesh industrial grade talc powder into 30 wt% sodium hydroxide solution at a solid-liquid ratio of 1 g:25 mL, stirring and heating at 90° C. (referred to as the first heating temperature in Table 1) for 4 h (referred to as the first heating time in Table 1), and then centrifuging, and vacuum drying the separated solid at 80° C. for 48 h to obtain hydroxylated talc powder; (2) Hydroxylated talc was added to an ethanol aqueous solution (prepared by ethanol and water in a volume ratio of 7.5:1) at a solid-liquid ratio of 1:7.5, and glacial acetic acid was added to adjust the pH to 3.8, and then a silane coupling agent was added. The mixture was heated in a water bath at 80°C (referred to as the second heating temperature in Table 1) and stirred for 4 h (referred to as the second heating time in Table 1). After stirring, the mixture was cooled to room temperature, and modified talc was obtained after centrifugal separation, washing and vacuum drying. The amount of the silane coupling agent was 5% of the weight of the hydroxylated talc, and KH570 was selected as the silane coupling agent.
[0033] As shown in Table 1, the difference between Preparation Examples 1-3 is that the production and processing parameters of the modified talc powder are different.
[0034] Table 1
[0035] Preparation Example 4 The difference between this preparation example and preparation example 3 is that the silane coupling agent is prepared by mixing KH570 and docosyltriethoxysilane in a weight ratio of 1:1.2.
[0036] As shown in Table 2, the difference between Preparation Examples 4-8 is that KH570 and docosyltriethoxysilane are mixed in different weight ratios (referred to as silane ratio in Table 2).
[0037] Table 2 Silane ratio
[0038]
[0039] As shown in Table 3, the difference between Preparation Examples 8-12 is that the amount of silane coupling agent used is different in percentage of the weight of hydroxylated talc powder (referred to as silane ratio in Table 3).
[0040] Table 3 Silane ratio
[0041] Example
[0042] Examples 1-5 The following description is given by taking Example 1 as an example.
[0043] Example 1
[0044] High temperature resistant and anti-debonding environmentally friendly degradable tape.
[0045] In this embodiment, the biodegradable resin for preparing the substrate layer is mixed with PBAT and PLA in a weight ratio of 70:25, the PBAT model is 1908, and the melt index is 4.85±0.13g / 10min; the PLA is LX175, and the melt index is 4.71±0.21g / 10min. The filler of the substrate layer is 2500 mesh wollastonite fiber, and the chain extender is ADR-4468.
[0046] In this embodiment, the high temperature resistant and anti-debonding environmentally friendly degradable adhesive tape is prepared according to the following steps: (1) Preparation of substrate layer: blend the biodegradable resin, filler and chain extender in a weight ratio of 95:5:0.5, melt extrude at 180±10°C and a main engine speed of 110 r / min, and then water-cool granulate to obtain a biodegradable composite. Blow film process the biodegradable composite at 150±5°C to obtain a substrate layer with a thickness of 50 μm for standby use; (2) Preparation of pressure-sensitive adhesive: acrylic acid monomer, initiator and tackifier were added to ethyl acetate, stirred and heated at 80°C for 6 h, then cooled to 20°C, and the resultant was mixed with xylene at a weight ratio of 1:1, and aziridine equivalent to 0.8% of the weight of xylene was added to obtain a pressure-sensitive adhesive; the ratio of acrylic acid monomer to ethyl acetate was 1 kg:2.6 L, the acrylic acid monomer contained 1.3 wt% (referred to as the acrylic acid ratio in Table 4) of acrylic acid, and the rest was composed of 2-(4-(6-nitrogen)-2-ol)-1-nitropropene in a weight ratio of 3:1:1. The mixed isooctyl acrylate, butyl acrylate and vinyl acetate are supplemented to 100%; the initiator is AIBN, and the amount of the initiator is 0.50% of the total weight of the acrylic monomer; the tackifier is the modified talc powder of Preparation Example 1 and commercially available alkali lignin (cas: 8068-05-1), the amount of the modified talc powder is 2.2% of the total weight of the acrylic monomer (referred to as the modified talc powder ratio in Table 4), and the amount of alkali lignin is 1.2% of the total weight of the acrylic monomer (referred to as the alkali lignin ratio in Table 4); (3) The pressure-sensitive adhesive is coated on the surface of the substrate layer at a coating thickness of 30 μm to obtain a semi-finished tape, and the semi-finished tape is dried at 95° C. for 10 minutes to obtain a high-temperature resistant and anti-debonding environmentally friendly degradable tape.
[0047] As shown in Table 4, the differences between Examples 1-5 are mainly in the different proportions of acrylic acid, modified talc and alkali lignin.
[0048] Table 4 Proportion of acrylic acid, modified talc and alkali lignin
[0049] Example 5-12 As shown in Table 5, the difference between Examples 5-16 is that the preparation examples of modified talc are different.
[0050] Table 5 Preparation example of modified talc
[0051] Embodiment 17
[0052] The difference between this embodiment and embodiment 16 is that BPO is used as the initiator.
[0053] As shown in Table 6, the difference between Examples 17-21 is that the percentage of the amount of initiator used in the total weight of the acrylic acid monomer (referred to as the initiator ratio in Table 6) is different.
[0054] Table 6 Proportion of initiators
[0055] Embodiment 22
[0056] Compared with Example 19, the acrylic monomer in this example contains 2.5 wt % of acrylic acid and 0.5 wt % of hydroxyethyl acrylate, and the rest is made up to 100% by isooctyl acrylate, butyl acrylate and vinyl acetate mixed in a weight ratio of 3:1:1.
[0057] As shown in Table 7, the difference between Examples 22-26 is that the proportion of hydroxyethyl acrylate in the acrylic monomer is different.
[0058] Table 7 Proportion of Hydroxyethyl Acrylate
[0059] Comparative Example Comparative Example 1
[0060] The difference between this comparative example and Example 1 is that the acrylic monomer does not include acrylic acid, and no tackifier is added during the preparation of the pressure-sensitive adhesive.
[0061] Comparative Example 2 This comparative example is different from Example 1 in that the acrylic monomer does not include acrylic acid.
[0062] Comparative Example 3 The difference between this comparative example and Example 1 is that the only tackifier added during the preparation of the pressure-sensitive adhesive is modified talc.
[0063] Comparative Example 4 The difference between this comparative example and Example 1 is that the only tackifier added during the preparation of the pressure-sensitive adhesive is alkali lignin.
[0064] Performance testing methods
[0065] 1. Heat resistance A 200mm×25mm tape was pasted on a mirror stainless steel plate washed with alcohol, rolled back and forth 3 times with a 2kg roller, and then left to stand at 25°C for 20 minutes, and then placed in an oven and baked at 180°C. The time when the tape was thermally peeled (i.e., the stickiness disappeared) was recorded as the thermal failure time. According to the above method, a group of tests was arranged for each embodiment and comparative example, and 10 parallel samples were set in each group. The average value of each group of 10 samples was taken as the result of the thermal failure time. Then, the thermal failure time of comparative example 1 was used as the benchmark to calculate the ratio of the thermal failure time of each embodiment and comparative example to the thermal failure time of comparative example 1, and the ratio was recorded as the relative heat resistance rate. The results are shown in Table 8.
[0066] 2. Adhesion performance Referring to GB / T 31125-2014 “Test method for initial tack of adhesive tapes - Ring method”, a group of tests was arranged for each embodiment and comparative example, and 10 parallel samples were set in each group. The average value of each group of 10 samples was taken as the result of the initial tack. The initial tack of comparative example 1 was used as a benchmark to calculate the ratio between the initial tack of each embodiment and comparative example and the initial tack of comparative example 1. The ratio was recorded as the relative initial tack. The results are shown in Table 9.
[0067] With reference to GB 2792-1998 "Test method for 180 peel strength of pressure-sensitive adhesive tape", a group of tests was arranged for each embodiment and comparative example, and 10 parallel samples were set in each group. The average value of each group of 10 samples was taken as the result of the holding force, and the holding force of comparative example 1 was used as a benchmark to calculate the ratio between the holding force of each embodiment and comparative example and the holding force of comparative example 1. The ratio was recorded as the relative holding force. The results are shown in Table 8.
[0068] Table 8 Test results
[0069] Combining Examples 1-5 and Comparative Example 1 and Table 8, it can be seen that compared with Comparative Example 1, the heat resistance of Examples 1-5 is generally significantly improved, and the improvement rate increases with the increase in the amount of acrylic acid and tackifier. While the heat resistance is improved, the holding force of the tape also increases significantly, and the initial adhesion does not decrease significantly, indicating that the present application not only overcomes the defect of poor heat resistance of the tape in the related art, but also better balances the initial adhesion and the holding force, so that the tape has better bonding performance.
[0070] It can be seen from Example 1 and Comparative Examples 2-4 and Table 8 that when any one of acrylic acid, modified talc and alkali lignin is missing, the heat resistance of the tape is difficult to be sufficiently improved.
[0071] It can be seen from Examples 5-7 and Table 8 that adjusting the production and processing parameters within the range of Preparation Examples 1-3 does not have a significant effect on the results.
[0072] It can be seen from Example 7, Examples 8-12 and Table 8 that the addition of docosyl triethoxysilane, especially when KH570 and docosyl triethoxysilane are mixed in a weight ratio of 1:(2.1-3.4), helps to improve the initial adhesion of the pressure-sensitive adhesive.
[0073] It can be seen from Examples 12-16 and Table 8 that, under the above silane coupling agent composition conditions, setting the amount of the silane coupling agent to 12-20% by weight of the hydroxylated talc powder helps to further improve the initial adhesion of the pressure-sensitive adhesive.
[0074] Combining Example 16, Examples 17-21 and Table 8, it can be seen that compared with AUBN, BPO is more helpful in improving the initial adhesion of the pressure-sensitive adhesive, and when the amount of BPO used is 0.75-1.10% of the total weight of the acrylic monomer, the initial adhesion of the pressure-sensitive adhesive is higher.
[0075] It can be seen from Example 21, Examples 22-26 and Table 8 that the addition of hydroxyethyl acrylate not only increases the cohesion of the system and improves the holding strength of the pressure-sensitive adhesive, but also has a certain effect on improving the initial adhesion of the pressure-sensitive adhesive. This effect is more obvious when the acrylic monomer contains 1.5-2.5wt% of hydroxyethyl acrylate.
[0076] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a high temperature resistant and anti-debonding environmentally friendly degradation tape, characterized in that: The following steps are involved: (1) Preparation of substrate layer: blending a degradable resin, a filler and a chain extender, and then melt-extrude the mixture, and then water-cooling and granulating the mixture to obtain a degradable composite, and then blowing the degradable composite to obtain a substrate layer for later use; the degradable resin includes PBAT and PLA; (2) Preparation of pressure-sensitive adhesive: adding acrylic monomer, initiator and tackifier to ethyl acetate, stirring and heating first, and then adding cross-linking agent after cooling and dilution to obtain pressure-sensitive adhesive; the tackifier includes modified talcum powder and alkali lignin, the modified talcum powder is talcum powder with allyl groups grafted on the surface of particles, the acrylic monomer contains at least one acrylate and 1.3-2.5wt% of acrylic acid, the amount of modified talcum powder is 2.2-2.8% of the total weight of acrylic monomer, and the amount of alkali lignin is 1.2-1.6% of the total weight of acrylic monomer; (3) coating the pressure-sensitive adhesive onto the surface of the substrate layer to obtain a semi-finished adhesive tape, and drying the semi-finished adhesive tape to obtain a high-temperature resistant and anti-debonding environmentally friendly degradable adhesive tape.
2. The method for preparing the high temperature resistant and anti-debonding environmentally friendly degradation tape according to claim 1, characterized in that: The modified talcum powder is prepared according to the following method: (1) adding talc to a sodium hydroxide solution, stirring and heating at 90-95° C. for 4-6 hours, and then centrifuging, and vacuum drying the separated solid to obtain hydroxylated talc; (2) Adding hydroxylated talc to an ethanol aqueous solution, adding glacial acetic acid to adjust the pH, then adding a silane coupling agent, stirring for 4-6 hours in a water bath at 80-85° C., cooling to room temperature after stirring, and obtaining modified talc after centrifugal separation, washing and vacuum drying; the amount of the silane coupling agent is 5-20% by weight of the hydroxylated talc, and the silane coupling agent has an allyl group in its molecule.
3. The method for preparing the high temperature resistant and anti-debonding environmentally friendly degradation tape according to claim 2, characterized in that: The silane coupling agent includes KH570.
4. The method for preparing the high temperature resistant and anti-debonding environmentally friendly degradation tape according to claim 3, characterized in that: The silane coupling agent is prepared by mixing KH570 and docosyltriethoxysilane in a weight ratio of 1:(1.2-3.4).
5. The method for preparing the high temperature resistant and anti-debonding environmentally friendly degradation tape according to claim 4, characterized in that: The silane coupling agent is prepared by mixing KH570 and docosyltriethoxysilane in a weight ratio of 1:(2.1-3.4).
6. The method for preparing the high temperature resistant and anti-debonding environmentally friendly degradation tape according to claim 5, characterized in that: The amount of the silane coupling agent used is 12-20% by weight of the hydroxylated talc.
7. The method for preparing the high temperature resistant and anti-debonding environmentally friendly degradation tape according to claim 1, characterized in that: The initiator is selected from one of BPO and AIBN.
8. The method for preparing the high temperature resistant and anti-debonding environmentally friendly degradation tape according to claim 7, characterized in that: The initiator is BPO, and the amount of BPO used is 0.75-1.10% of the total weight of the acrylic acid monomers.
9. The method for preparing the high temperature resistant and anti-debonding environmentally friendly degradation tape according to claim 1, characterized in that: The acrylic acid monomer contains 0.5-2.5 wt % of hydroxyethyl acrylate.
10. The method for preparing the high temperature resistant and anti-debonding environmentally friendly degradation tape according to claim 8, characterized in that: The acrylic acid monomer contains 1.5-2.5 wt % of hydroxyethyl acrylate.